Preventing the next pandemic - Bett, Bernard K. (2022)
In this episode of Africa Science Focus, we find out how scientists are taking on this critical issue through farming. Bernard Bett at the International Livestock Research Institute, in Nairobi, Kenya, introduces us to the concept of one health – an intervention approach that recognises the connection of people, animals and plants.